The naughtiest girl marches on - Digby, Anne (Hodder Children's London, 1999)
Elizabeth is appointed monitor again, but one of the 2nd form boys is turning all of the other boys against her. Elizabeth decides to investigate with the help of her friends - can she find out who has a grudge against her and why?